Antibacterial PET-Silk fabric containing Salvia officinalis extract. Issue 2 (17th February 2019) - Jafari Khosroabadi, Anis; Hemmatinejad, Nahid; Bashari, Azadeh
ABSTRACT: In this study, novel PET-Silk fabric is introduced via finishing PET fabric with silk hydrogel and Salvia officinalis extract. The silk hydrogel was prepared from waste silk; morphology and chemical structure were evaluated by scanning electron microscopy, X-ray diffraction, and Fourier transform infrared spectroscopy methods. The results indicated the 3D porous network and crystalline structure of hydrogel. The polyester fabric was finished with prepared hydrogel. Contact angle and water uptake of modified fabric were assessed. S. officinalis extract was used as an antibacterial agent. Results of antibacterial tests confirmed a remarkable antibacterial effect of finished fabrics with the extract.